Performance, emission and combustion analysis of diesel engine fuelled with emulsified biodiesel. (21st June 2019) - Gopidesi, Radha Krishna; Premkartikkumar, S.R.
The present investigation is mainly focused on the reduction of NOX emissions from the diesel engine. In this experimental work, the diesel engine has initially run by diesel alone, secondly, 10% cottonseed methyl ester biodiesel (B10) and finally emulsion of 10% water with B10 (WiB10E) in combination. The emulsified biodiesel WiB10E shows the maximum reduction of NOX emissions in comparison with the pure diesel and B10 fuel operations. Also, due to the cooling effect provided by the water in the combustion chamber, the WiB10E shows the slight increase of the HC and CO emissions. Since WiB10E fuel has a boiling point difference, it leads to secondary atomisation. The WiB10E has shown the higher cylinder pressure of 65.92 bars at a crank angle of 366° due to microexplosion. Hence, emulsified biodiesel fuel is efficient in the reduction of NOX emissions amongst all the techniques.